Is it possible to perform forensic human identification by calculating fractal dimensions? A pilot study in panoramic radiographs - Annie Seabra de Medeiros; Vanessa Moreira Andrade; Andreia Cristina Breda de Souza; Maria Augusta Visconti (Egyptian Journal of Forensic Sciences)
Abstract Background Fractal analysis is an important descriptor of bone complexity. This pilot study aimed to verify the possibility of using fractal dimension as an additional resource in human identification. A total of 15 pairs of panoramic radiographs were selected from the same individual, each with images acquired at different times (1, 3, and 5 years apart). Initially, seven standardized regions of interest were selected: mandibular head and angle, alveolar bone between the second premolar and first lower molar, symphysis, maxillary tuberosity, anterior nasal spine, and a random region with differentiated trabeculate. This last region was called “the specific trabeculation region” and should represent a particular architecture of the individual under analysis, regardless of the anatomical location. The fractal dimension and mean gray values were calculated to determine the absolute difference between the pairs of examinations. Results When comparing the panoramas of the same individual, there was no statistical difference (p = 0.067 for fractal dimension and p = 0.251 for mean gray value) for any of the regions tested. The specific trabecular region presented less variability in measurements between times in both analyses. The correlation between fractal dimension and mean gray value was only significant for the angle region (r = 0.542; p = 0.037). Conclusions It was concluded that the fractal dimension calculation can be an additional, promising, low-cost, and easy-to-perform resource in forensic human identification processes. Furthermore, this measurement can be performed in the specific trabecular region at the examiner’s discretion, thus facilitating the analysis process.